Identification of a novel melittin isoform from Africanized Apis mellifera venom - Sciani, Juliana Mozer; Marques-Porto, Rafael; Lourenco Junior, Airton [UNESP]; Orsi, Ricardo de Oliveira; Ferreira Junior, Rui Seabra [UNESP]; Barraviera, Benedito [UNESP]; Pimenta, Daniel Carvalho [UNESP] (Elsevier B.V., 2010)
Apis mellifera, the European honey bee, is perhaps the most studied insect in the Apidae family. Its venom is comprised basically of melittin, phospholipase A(2), histamine, hyaluronidase, cathecolamines and serotonin. Some of these components have been associated to allergic reactions, among several other symptoms. on the other hand, bee mass-stinging is increasingly becoming a serious public health issue; therefore, the development of efficient serum-therapies has become necessary, with a consequent better characterization of the venom. In this work, we report the isolation and biochemical characterization of melittin-S, an isoform of melittin comprising a Ser residue at the 10th position, from the venom of Africanized A. mellifera. This peptide demonstrated to be less hemolytic than melittin and to adopt a less organized secondary structure, as assessed by circular dichroism spectroscopy. Melittin-S venom contents varied seasonally, and the maximum secretion occurred during the (southern) winter months. Data on the variation of the honey bee venom composition are necessary to guide future immunological studies, aiming for the development of an efficient anti-serum against Africanized A. mellifera venom and, consequently, an effective treatment for the victims of mass-stinging. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Apis mellifera; Melittin; Venom; Seasonal variation; Peptides; Natural peptides